The Lexical Morpheme Acquisition of a Learner of English as a Second Language - Burhansyah, Burhansyah (University of Muhammadiyah Prof. DR. HAMKA, 2018)
The present study aims to examine the acquisition of English lexical morphemes - i.e. past –ed marker and plural –s marker on nouns, in L2 (second language) English within the framework of Processability Theory (henceforth PT). The participant of this research was LE, an Indonesian learner learning English as L2 in an instructional context. The data in the form of essay written by LE was collected longitudinally at four points in time during the period of four months. Based on the data, a distributional analysis was carried out, and then the findings were analysed by using the implicational scaling in accordance with the emergence criterion in order to determine the points of acquisition of the two morphological forms under scrutiny. The research finding indicates that the acquisition points of the lexical morphemes appear to follow PT’s predictions, where the emergence point of past –ed marker and plural –s marker occurred at comparatively the same point in time as hypothesised in PT. Moreover, the finding of this research reveals that the predictions of PT seem to be followed in L2 written English; it indicates PT’s capacity to account for morphological acquisition in both written and spoken language production.        Keywords: processability theory, L2 acquisition, lexical morpheme